Employing data engineering on regional container lines{u2019} intermodal and job offer system (IJS) module and implementation of RCL-GPT : a CHATGPT knowledge for RCL - Salera, Marie Curie Olar; Chutiporn Anutariya; Vatcharaporn Esichaikul; Chaklam Silpasuwanchai; Regional Container Lines PCL (RCL) (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Organizations with a wide range of operations must manage a multitude of services and processes. Every organization must be able to track both the services it provides and its overall performance. Unpredictable issues can disrupt business operations; therefore, preventing and mitigating these issues is critical. The goal of this study is to apply data engineering to one of the 27 modules of Regional Container Lines, Intermodal, and Job System. Data engineering includes, but is not limited to, data profiling, data cleaning, data warehouse design, and incremental ETL. Once this is in place, the organization will be able to analyze data to aid in decision making. ChatGPT, on the other hand, took the world by storm when it was released in November 2022. Several use cases for how ChatGPT can be used in various domains to improve their work have been identified, and several companies have integrated this into their products. As a result, the organization will create its own ChatGPT-based application, RCL-GPT, to support employee training and process standardization, with ChatGPT technology at its core.
An Internship report submitted in partial fulfillment of the requirements for the degree of Master of Science in Information Management, School of Engineering and Technology
Internship Report (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Regional container lines (Firm); ChatGPT; Artificial intelligence; Human-computer interaction